Linking Employee Commitment, Workplace Reward And Career Development To Quality Of Work Life - et. al., Mary Shadrach Omofowa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study examines the relationship between employee commitment, workplace reward, career development and quality of work life. Using the social exchange lens, we developed hypotheses that focus on employee commitment, workplace reward, career development and their effects on quality of work life. The authors surveyed 350 employees in 30 insurance companies operating in Nigeria. Data from 350 employees reveals that employee commitment significantly influences quality of work life. Workplace reward has a significant effect on quality of work life. Further, career development promotes quality of work life. These results clarify the role employee commitment, workplace reward and career development play in fostering quality of work life in the emerging market context. The results of the study, limitations and suggestions for future studies are presented.